Análisis de la autoevaluación institucional en el mejoramiento de la gestión escolar del colegio de bachillerato Libertad en la ciudad de Latacunga - Molina Sánchez, Silvio Raúl (2016)
The following research work aims to contribute to the process of Institutional Self -Assessment in the Libertad High School, with the development of a protocol that will guide to these processes are carried out in organized way and provide reliable and useful information, making important decisions that contribute to the continuous improvement of the quality of education imparted in the institution. To achieve this goal several bibliographical sources was analyzed and institutional self-assessment surveys were developed to people concerned with the education of the campus, after I detected the priority problems in the institution. Then I proposed as solution providing the Protocol processes Institutional self-evaluation to the College, which includes six important steps for the process, to proceed efficiently and with the cooperation of all people that make up the institution. Once delivered the work done, the acceptance of the document by the Rector of the institution was taken, indicating that will be used at a later Self- assessment, in which all aspects mentioned in the protocol will be considered.